EFFECT OF PROCUREMENT OUTSOURCING ON PERFORMANCE OF KENYA AIRWAYS LIMITED - Kabachia, Sheila; Kihara, Dr. Allan (International Journal of Supply Chain and Logistics, 2019)
Purpose: The study sought to establish the effects of procurement outsourcing on performance of firms in the airline industry in Kenya with a focus on Kenya Airways Limited. The study specifically looked at the effect of purchasing functions outsourcing, transport and logistics services outsourcing, warehousing services outsourcing and procurement information systems management outsourcing on performance of firms in the airline industry with a focus on Kenya Airways Company Limited. Methodology: The study was guided by Transaction Cost Theory, SCOR Model, the Principal Agency Theory and Resource Dependency Theory. A case study was adopted in the study as a research design and targeted 75 employees in procurement and logistics departments at Kenya Airways Company departments. The study adopted a census technique with respect to the unit of analysis which was Kenya Airways Company Limited. The study used both descriptive as well as inferential statistics for analysis. Descriptive statistics of frequency distributions, percentages and frequency tables were used while inferential statistics of correlation and regression analysis were employed using SPSS version 24.0 to establish the relationship between procurement outsourcing practices and performance of firms in the airline industry. Results: The findings of the study revealed that purchasing functions outsourcing, transport and logistics services outsourcing, warehousing services outsourcing and procurement information system management outsourcing positively and significantly affect performance of firms in the airline industry. Contributions to policy and practice: The study recommends that Kenya Airways Limited should focus on outsourcing purchasing functions since the practice positively and significantly affects performance of the firm. The study also recommends that Kenya Airways Limited should enhance transport and logistics outsourcing since the practice positively and significantly affects performance of the firm. The study further recommends that Kenya Airways Limited should promote outsourcing of warehousing services since the practice positively and significantly affects performance of the firm. The study finally recommends that Kenya Airways Limited should enhance outsourcing of procurement information system management since the practice positively and significantly affects performance of the firm.